Return to Play and Career Length following Hip Arthroscopy in Professional Baseball Players. Issue 7 (21st July 2017) - Mannava, Sandeep; Frangiamore, Salvatore Joseph; McNamara, Shannen; Menge, Travis J.; Briggs, Karen K.; Philippon, Marc J.
Objectives: Hip arthroscopy is a highly effective treatment for symptomatic femoroacetabular impingement (FAI). High level, professional athletes have been able to return to their professional sport following arthroscopic hip surgery intervention. To date, there is a paucity of literature related to professional baseball player's ability to return to sport following hip injury as a result of FAI. The purpose of this study was to determine the rate of return to play and length of career in professional baseball players following hip arthroscopy for FAI. We hypothesized that professional baseball players were able to return to the same level of pre-surgical competition following FAI arthroscopic hip surgery for a sustained period of time. Methods: 44 professional baseball players (51 hips) underwent hip arthroscopy for FAI between 2000 and 2015 by a single surgeon. Return to play was defined as a player competing in a pre-season or regular season minor or major league baseball game following surgery. Data was obtained for each player from MLB.com, MiLB.com, Baseballreference.com and individual team websites. Results: The average age of players at the time of arthroscopy was 26.6 years (18 to 38 years;StDev=4.8). No players had bilateral arthroscopy on the same day. Of the 44 players, 24 were pitchers and 27 were position players (12 infielders, 10 outfielders, 5 catchers). In hitters, 74% (20/27) of the procedures involved the front side hip of their batting stance. In pitchers, 71% (17/24) of procedures involved the lead leg of their pitching stance. Average career length prior to hip surgery was 6.2 years (range 1-20 years;stdev=5.1). Following hip arthroscopy, 96% (49/51) returned to professional baseball after each hip arthroscopy. Those who returned played for an average of 3.6 seasons (range 1 to 14 seasons;stdev=2.9) after hip arthroscopy. The average career length of players in this cohort was 10 seasons (range 1 to 21;stdev=5). There was no difference in the years played after arthroscopy by position (pitchers average =3.3(stdev=2.5) years and position players average = 3.9 (stdev=3.2) years) (p=0.48). Conclusion: Professional baseball players who underwent hip arthroscopy were able to return to the same high level of competition after surgery. Pitchers were more likely than position players to undergo surgical intervention with hip arthroscopy. Irrespective of player position, hip arthroscopy seems to be a surgical intervention that can allow for treatment of FAI pathology in a minimally invasive manner, while allowing for return to professional competition following full recovery. As hip arthroscopy continues to evolve, future interventions may improve post-operative return to play in baseball—lengthening playing career and level of play. At this time, hip arthroscopy is an effective surgical intervention that allows players to return to their professional level of baseball play.